(untitled) (Journal of the College of Basic Education, 2023)
The aim of the research is to identify the effect of the Jigsaw strategy (:118587) compared to the traditional methodIn the collection of physics and science processes for the first intermediate grade students in Fatima High SchoolAl-Zahraa for girls affiliated to the General Directorate of Education in Anbar Governorate, from the four seasonsThe first for the physics textbook from the first semester of the year 2014-2012, as it reached a sampleThe research was (62) female students, with (31) for A-section and (21) for C-section, and the repeaters who were excludedStatistically, for the purpose of ensuring parity, because they have more experience than their new colleaguesFor the purpose of fixing the equivalence of the research groups, their reward was verified in the following variablesChronological age in months, achievement in science for the sixth grade, and informationThe previous study showed that the use of the strategy in teaching physics led to superiorityThe experimental group over the control group in achievement and science processes.